DATA PROCESSING SYSTEM CHECK_LIST PT. GAMYA - Yoga Perdana; Eko Hadiyanto. SSi. MM (Jurnal Sistem Informasi, 2000)
The process of the work done by officers who are still checking with how to writereports done manually, so in that its data will have difficulty finding the car willoperate.Given the data processing system check- list of authors is expected to help create therelevant parties to perform daily activities.Information processing the required data can then be displayed each time inaccordance with the request.